1976
DOI: 10.1111/j.1600-0404.1976.tb04799.x
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic Changes in Automechanics With Increased Heavy Metal Levels

Abstract: Twenty automechanics possessing increased whole blood values of one or more of the following heavy metals; chromium, copper, lead, manganese and nickel, were studied for peripheral nerve affection by means of electromyography (both sensoric and motoric nerve potentials were recorded). The heavy metal contents were related to the findings of denervation, distal motor latency, distal sensory latency, motoric and sensoric conduction velocities. Apart from two workers, in whom only lead was assayed, the remaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Similar studies (Amvig et al, 1980;Grandjean et al , 1978;Haenninen et al , 1978;Mantere et al , 1982;Valciukas et al , 1978) have found disturbances in visual motor performance, IQ test performance, hand dexterity, mood, nervousness and coping in lead workers with blood lead levels of 50 to 80 J,Lg/dL. Similarly, Melgaard et al (1976) observed a clear association between lead exposure and peripheral nerve dysfunction in automobile mechanics exposed to tetra-ethyl lead and other compounds in lubricating and high-pressure oils. (1976) found no differences between control and lead-exposed workers as judged by numerous psychometric and other performance tests.…”
Section: Non-carcinogenic Effectsmentioning
confidence: 60%
“…Similar studies (Amvig et al, 1980;Grandjean et al , 1978;Haenninen et al , 1978;Mantere et al , 1982;Valciukas et al , 1978) have found disturbances in visual motor performance, IQ test performance, hand dexterity, mood, nervousness and coping in lead workers with blood lead levels of 50 to 80 J,Lg/dL. Similarly, Melgaard et al (1976) observed a clear association between lead exposure and peripheral nerve dysfunction in automobile mechanics exposed to tetra-ethyl lead and other compounds in lubricating and high-pressure oils. (1976) found no differences between control and lead-exposed workers as judged by numerous psychometric and other performance tests.…”
Section: Non-carcinogenic Effectsmentioning
confidence: 60%
“…Manganese and nickel can, like lead, give rise to peripheral neuropathy and brain damage (Tolonen, 1972). Our recent electrophysiological investigation (Melgaard et al, 1976b) showed peripheral nerve abnormalities in autoworkers with high heavy metal levels. The high levels of nickel, chromium and manganese among the autoworkers underlines the need for scrupulous hygiene in autoworkshops.…”
Section: Cdustmentioning
confidence: 81%
“…The heavy metal content and ALAD activity of whole blood from the control group has been previously defined (Melgaard et al, 1976a). The lead content and ALAD activity in the blood of autoworkers is shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Assay of 8-aminolevulinic acid dehydratase (ALAD) activity and lead content in whole blood and determination of &-aminolevulinic acid (ALA) in urine have been described previously (Melgaard et al, 1976a). Lead in dust and oil samples (about 30 mg) was extracted by heating them twice to 100°C for two hours with 2 ml concentrated hydrochloric acid-nitric acid (1 :1) mixture.…”
Section: Biochemical Assaysmentioning
confidence: 99%
See 1 more Smart Citation